A Highly Sensitive and Recyclable Ln‐MOF Luminescent Sensor for the Efficient Detection of Fe3+ and CrVI Anions. Issue 20 (13th September 2019) - Li, Xiao; Tang, Jixin; Liu, Han; Gao, Kuan; Meng, Xiangru; Wu, Jie; Hou, Hongwei
Abstract: Two new three‐dimensional (3D) Ln III metal‐organic frameworks (MOFs) were designed and successfully obtained via a solvothermal reaction between lanthanide(III) nitrates and a semi‐flexible carbazole tetracarboxylate acid linker as a high‐performance chromophore.1 and2 possess porous 3D networks with channels along the a axis, and more importantly, they show a highly sensitive and selective fluorescence quenching response to Fe 3+ and Cr VI anions. The sensing mechanism investigation revealed that the weak interactions of Fe 3+ with nitrogen atoms of carbazole and deprotonated carboxylic acids protruding into the pores of MOFs quenched the luminescence of1 and2 effectively. In addition, the competition absorption also played an important role in the luminescence quenching detection of Fe 3+ based on1, and Cr VI anions based on1 and2 . Therefore, 1 and2 represent an alternative example of regenerable luminescence based sensors for the quantitative detection of Fe 3+ and Cr VI anions. Abstract : Luminescence and sensing properties of Ln‐MOFs1 and2 showed a highly sensitive, selective, and recyclable fluorescence quenching response to Fe 3+ cations and Cr VI anions.